Increased Cholinergic Tone Causes Pre-synaptic Neuromuscular Degeneration and is Associated with Impaired Diaphragm Function - Magalhães-Gomes, Matheus P.S.; Camargos, Wallace; Valadão, Priscila A.C.; Garcias, Rubens S.; Rodrigues, Hermann A.; Andrade, Jéssica N.; Teixeira, Vanessa P.; Naves, Lígia A.; Cavalcante, Walter L.G.; Gallaci, Marcia [UNESP]; Guatimosim, Silvia; Prado, Vânia F.; et al. (Elsevier, 2021)
In vertebrates, muscle activity is dependent on acetylcholine (ACh) released from neuromuscular junctions (NMJs), and changes in cholinergic neurotransmission are linked to a variety of neuromuscular diseases, including congenital myasthenic syndromes (CMS). The storage and release of ACh depends on the activity of the Vesicular Acetylcholine Transporter (VAChT), a rate-limiting step for cholinergic neurotransmission whose loss of function mutations was shown to cause human congenital myasthenia. However, we know much less about increased VAChT activity, due to copy number variations, for example. Therefore, here we investigated the impact of increased VAChT expression and consequently ACh levels at the synaptic cleft of the diaphragm NMJs. We analyzed structure and function of nerve and muscles from a mouse model of cholinergic hyperfunction (ChAT-ChR2-EYFP) with increased expression of VAChT. Our results showed a significant increase of ACh released under evoked stimuli. However, we observed deleterious changes in synaptic vesicles cycle (impaired endocytosis and decrease in vesicles number), together with structural alterations of NMJs. Interestingly, ultrastructure analyses showed that synaptic vesicles from ChAT-ChR2-EYFP mice NMJs were larger, which might be related to increased ACh load. We also observed that these larger synaptic vesicles were less rounded in comparison with control. Finally, we showed that ChAT-ChR2-EYFP mice NMJs have compromised safety factor, possible due to the structural alterations we described. These findings reveal that physiological cholinergic activity is important to maintain the structure and function of the neuromuscular system and help to understand some of the neuromuscular adverse effects experienced by chronically increased NMJ neurotransmission, such as individuals treated with cholinesterase inhibitors.
Keywords: acetylcholine; cholinergic signaling; neuromuscular junction